2020
DOI: 10.1112/s0010437x20007071
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic directions of two-dimensional biholomorphisms

Abstract: We prove that for each characteristic direction $[v]$ of a tangent to the identity diffeomorphism of order $k+1$ in $(\mathbb{C}^{2},0)$ there exist either an analytic curve of fixed points tangent to $[v]$ or $k$ parabolic manifolds where all the orbits are tangent to $[v]$, and that at least one of these parabolic manifolds is or contains a parabolic curve.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…is arbitrarily uniformly close to u and we have from (10) that this finite product is arbitrarily uniformly close to 1 if |x m y n | is small enough. Therefore, we can assume that ε is small enough so that |u(x, y) − 1| < 1/2 for all (x, y) ∈ U k .…”
Section: Remark 22 An Analogous Results Follows Formentioning
confidence: 94%
See 1 more Smart Citation
“…is arbitrarily uniformly close to u and we have from (10) that this finite product is arbitrarily uniformly close to 1 if |x m y n | is small enough. Therefore, we can assume that ε is small enough so that |u(x, y) − 1| < 1/2 for all (x, y) ∈ U k .…”
Section: Remark 22 An Analogous Results Follows Formentioning
confidence: 94%
“…In dimension two, no complete description of the dynamics of F is known. Some partial analogs of Leau-Fatou flower theorem have been obtained, guaranteeing either the existence of one-dimensional stable manifolds [4,6,1,10] or of twodimensional ones [7,14]. With no extra assumptions on F , the most general result is due to Abate [1], who showed that F always supports some stable dynamics: either F has a curve of fixed points or there exist one-dimensional stable manifolds of F with 0 in their boundary.…”
Section: Introductionmentioning
confidence: 99%
“…This allows to apply Hakim's result to get a parabolic curve for the lifted germs, transversal to the exceptional divisor of the modification, so that it descends to a parabolic curve for f$f$. Several authors addressed the problem of finding stable manifolds for (possibly non‐isolated) two$\text{two}$‐dimensional tangent to the identity germs, and the picture is quite complete now, see, for example, [1, 2, 10, 15, 18, 23, 24, 26, 29, 32, 38, 39]. The description of parabolic manifolds has been recently instrumental for the construction of examples of wandering domains, see [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Besides being only formal, the surface S$S$ is also singular, and [23] cannot be applied to f|S$f|_S$ even if S$S$ were convergent. When working on the model Xπ0$X_{\pi _0}$, the strict transform S$\widetilde{S}$ of S$S$ is smooth and invariant by the lift f$\widetilde{f}$ of f$f$.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation